On the general solution of first-kind hypersingular integral equations - Obaiys, Suzan Jabbar; Abbas, Zulkifly; Nik Long, Nik Mohd Asri; Ahmad, Ahmad Fahad; Ahmedov, Anvarjon; Raad, Haider Khaleel (Science Publications, 2016)
A new algorithm is presented to provide a general solution for a first type Hyper singular Integral Equation (HSIE). The singular integral has been converted into a regular form by cancelling the singularity and then transforming it into a system of algebraic equation based orthogonal poly- nomials. We applied the convergence method presented by (Obaiys, 2013) to conform the numerical solution of the regularized Hadamard equation, which has shown an absolute agreement with the exact solution within small values of n. The proposed method has been examined by various HSIEs where the displacement function satisfies the HÓ§lder-continuous first derivative. Such equations are particularly important inmany physics and engineering problems, such as fracture mechanics, acoustics and elasticity.